Questioning our faith in the judiciary: from institutional entrenchment to the monopoly of constitution - Carvalhaes, Rafael Bitencourt; Miranda Netto, Fernando Gama de (Revista de Investigações Constitucionais, 2022)
This paper intends to question the role of the Brazilian Supreme Federal Court as an agent of democratic construction and its role as guardian of the constitution. The interest in the Supreme Court is due to the political arrangement and the overlapping of powers and functions of the court than the other powers. A Constitutional Court with inflated powers can lead to democratic dysfunction and judicial hegemony about institutions. Notably, an expansion of the Brazilian Supreme Federal Court’s powers should create a way for it to interpret the Constitution and its influence on the political process. There is no doubt that the Brazilian Supreme Federal Court has become an important political actor, making it present in almost all legal and political areas. However, constitutional monopoly, judicial activism, and excessive interference in the political process degenerate the original democratic model, deconstructing the excess of faith deposited in the judiciary.